Ultrasound Super‐Resolution Imaging of Neonatal Cerebral Vascular Reorganization - Simone Schwarz; Louise Denis; Emmanuel Nedoschill; Adrian Buehler; Vera Danko; Alina C. Hilger; Francisco Brevis Nuñez; Nikola R. Dürr; Martin Schlunz‐Hendann; Friedhelm Brassel; Ursula Felderhoff‐Müser; Heiko Reutter; et al. (Advanced Science)
Abstract During the first days of neonatal growth, the central nervous system (CNS) develops self‐regulatory mechanisms to ensure constant cerebral perfusion. However, this vascular neogenesis takes place at a microscopic scale that cannot be observed with current clinical imaging techniques. Ultrasound localization microscopy (ULM) allows us to observe micro‐vessels of the order of a few microns at depths of several centimeters. This can be done using conventional clinical ultrasound scanners and contrast sequences (CEUS). In this study, ULM is used to observe the human microvasculature in neonatal patients undergoing treatment for life‐threatening malformations forming direct connections between the cerebral arterial and venous systems. It is observed that neuroendovascular treatment of neonatal arteriovenous malformations causes remodeling and reorganization of the cerebral vasculature by also activating corticomedullary vascular connections. ULM enables us to follow microvascular changes in human neonates with high spatio‐temporal resolution. ULM may provide a novel clinical translatable tool, particularly including cerebral imaging in very young patients.